ANALISIS KINERJA APARATUR DESA DI KECAMATAN SULANG KABUPATEN REMBANG - Ahmad Nur Arifin; Ming Ming Lukiarti (Ikatan Dosen Menulis, 2026)
Village apparatus plays an important role in building and improving the welfare of village communities. This investigation was conducted to provide information on the impact of office facilities, work discipline, and work motivation on the performance of village officials. This investigative approach method involves a quantitative approach with subjective data and primary data types. The subject of this study is the village apparatus of Sulang District, Rembang Regency, which has 21 villages. Two types of variables are involved in this investigation: independent variables (office facilities, work discipline, and work motivation) and the dependent variable (village apparatus performance). The population includes 180 village officials from across Sulang District. The sampling method involved a saturated sample with an effective response rate (effective sample), resulting in a final sample size of 100 respondents (a response rate of 55.6% of the total population). Data collection was carried out using the survey method, utilizing a questionnaire instrument. The data analysis technique involves multiple linear regression analysis. This investigation found that office facilities and work motivation partially impact village apparatus performance, while work discipline partially does not affect village apparatus performance.